Disorientasi Politik dan Peran Intermediary Kelas Menengah To Pulo: Politik Lokal di Kepulauan Selayar Pasca Orde Baru - Bakar, Abu (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2015)
This paper discusses the emergence of social movements To Pulo with the issue of a new government and the development of the New Order. Today, the issue is increasingly disappearing in local political discourse in Kepulauan Selayar. This paper will explore how these things to happen to focus on the political disorientation and why the role of intermediary actors To Pulo weakened middle class. To explain this case, the use of social movement theory perspective of social identity theory and case study research method. The purpose of this paper to describe a social movement To Pulo by answering questions; how To Pulo social movements?; Why did political disorientation inside could be happened?; Why did middle-class intermediary role fizzle?. The conclusion is the disorientation caused by the absence of a strong commitment. And the weak role of the intermediary is caused by internal conflicts To Pulo.